Injections of predatory bacteria work alongside host immune cells to treat Shigella infection in zebrafish larvae - Willis, Alexandra R.; Moore, Christopher; Mazon-Moya, Maria; Krokowski, Sina; Lambert, Carey; Till, Rob; Mostowy, Serge; Sockett, R. Elizabeth (Elsevier (Cell Press), 2016)
Bdellovibrio bacteriovorus are predatory bacteria that invade and kill a range of Gram-negative bacterial pathogens in natural environments and in vitro [ 1 and 2]. In this study, we investigated Bdellovibrio as an injected, antibacterial treatment in vivo, using zebrafish (Danio rerio) larvae infected with an antibiotic-resistant strain of the human pathogen Shigella flexneri. When injected alone, Bdellovibrio can persist for more than 24 hr in vivo yet exert no pathogenic effects on zebrafish larvae. Bdellovibrio injection of zebrafish containing a lethal dose of Shigella promotes pathogen killing, leading to increased zebrafish survival. Live-cell imaging of infected zebrafish reveals that Shigella undergo rounding induced by the invasive predation from Bdellovibrio in vivo. Furthermore, Shigella-dependent replication of Bdellovibrio was captured inside the zebrafish larvae, indicating active predation in vivo. Bdellovibrio can be engulfed and ultimately eliminated by host neutrophils and macrophages, yet have a sufficient dwell time to prey on pathogens. Experiments in immune-compromised zebrafish reveal that maximal therapeutic benefits of Bdellovibrio result from the synergy of both bacterial predation and host immunity, but that in vivo predation contributes significantly to the survival outcome. Our results demonstrate that successful antibacterial therapy can be achieved via the host immune system working together with bacterial predation by Bdellovibrio. Such cooperation may be important to consider in the fight against antibiotic-resistant infections in vivo.